The Description Lifestyle of Elderly People with Hypertension - Erni Tri Indarti; Iin Alim Tias Putri (Master of Public Health Program Universitas STRADA Indonesia, 2026)
Physiologically, blood vessels tend to harden or stiffen with age. This hardening of the arteries forces the heart to work harder, leading to high blood pressure in older adults. An unhealthy lifestyle in older adults increases the risk of hypertension. The purpose of the study was to determine the lifestyle of elderly people with hypertension at the elderly health post in Panasan Hamlet, Tekenglagahan Village, Loceret District, Nganjuk Regency. This study used a descriptive design which was carried out on February 11, 2025 at the the elderly health post in Panasan Hamlet, Tekenglagahan Village, Loceret District, Nganjuk Regency. The population in this study were 40 elderly with hypertension. A sample of 40 respondents using the Total sampling technique. The research variable is lifestyle. Data collection using a questionnaire. The results of this study indicate that of the 40 respondents, the majority (28 respondents (70%) had a good lifestyle, and almost half (12 respondents (30%) had an unhealthy lifestyle. The results of this study were influenced by gender, age, occupation, and residence. A better lifestyle is more common in women because more household activities are carried out by women. Most have elementary school education, resulting in the elderly living a simple life with minimal stress, but a lack of understanding of healthy food consumed by the elderly, causing almost all of them to have poor eating habits. Working as farmers makes the elderly fulfill their physical activities and receive life support because they live at home with children.